The Ecstasy of Communication. Critical remarks on Jean Baudrillard - Pieter Duvenage (Communicare)
The socio-cultural criticism of Jean Baudrillard (born 1929), spans from the political turmoil of France in the late-1960s, to the mediatised world of the 1990s and early 21st century.1 In this process his provocative work on the socio-political role of signs, symbolic exchange, simulation, and hyperreality has important implications for communication studies – and more specifically communication theory. The point is that with the “… greater mediatization of society … we are witnessing the virtualization of our world.”2 This contribution briefly reconstructs, firstly, two phases in Baudrillard’s intellectual career – phases that shifted from an early neo-Marxist critique of the modern consumer society to a post-Marxist or postmodern view of society (which include engagements with socio-anthropology; psychoanalysis, sociology, semiology and media theory), and eventually ends in a kind of anti-theory with an extreme fatal vision of the world.3 In section 2 the implications of these two shifts in Baudrillard’s intellectual career are contextualized in the field of media and communication studies – and specifically his concept of the “ecstasy of communication”. Finally (in Section 3) some critical remarks are made on Baudrillard’s fascinating, but problematic, project.